(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Epstein-Barr virus (EBV) is one of the most common latent viruses inside the humans’ B-lymphocytes and it has been documented as a causative agent of many cancers. The virus may be transmitted when infected blood transfused to immunocompromised as well as immunocompetent individuals. Objective: To estimate the prevalence of EBV among apparently healthy blood donors by enzyme-linked immunosorbent assay (ELISA) and by quantitative real time polymerase chain reaction (RT-PCR). Methods: Four hundred fifty (450) blood donors were enrolled in this study. Plasma samples were screened by ELISA technique for detection of EBV viral capsid antigen (VCA-IgG). DNA extracted from 50 representative samples of these 450, and plasma EBV viral load was investigated by RT-PCR. Results: The overall sero-prevalence of EBV IgG was 79.8%, with a significantly higher prevalence among females than males. RT-PCR results were negative for all of the 50 representative samples. Conclusion: The high EBV sero-prevalence rates among Iraqi subjects raise the possibility of increasing the risk of EBV-associated malignant diseases. Keywords: Epstein-Barr virus, seroprevalence, VCA-IgG, real-time PCR, blood donors Citation: Amjad Q. Redha, Asmaa B. Al-Obaidi, Haider F. Ghazi, Haider S. Kadhim. Sero-prevalence and plasma viral load of Epstein Barr virus among Iraqi blood donors. Iraqi JMS. 2017; Vol. 15(2): 135-142. doi: 10.22578/IJMS.15.2.5